Illustrating Concepts and Phenomena in Psychology A Teacher-Friendly Compendium of Examples - Cameron, E. Leslie; Bernstein, Douglas A. (Cham : Springer International Publishing : Imprint: Springer, 2022)
This compendium of examples of psychological concepts and phenomena is designed to make it easier for both novice and experienced teachers of psychology at all levels to bring new and/or particularly illuminating examples to their lectures and other presentations. Psychology instructors know that vivid examples bring concepts to life for students, making psychology both more accessible and interesting. Having a good supply of such examples can be particularly important when, as often happens, students fail to immediately grasp particular points, especially those that are complex or difficult. Generating compelling examples can be challenging, particularly when teaching a course, such as Introductory Psychology, in which much of the material is outside one's main area of expertise, when teaching a course for the first time, or when teaching a course that is entirely outside one's main area of expertise. This compendium will serve as a one-stop reference that presents a topic-organized body of compelling examples that instructors can explore as they prepare their teaching materials. The examples they will find range from simple illustrations (e.g., muting an obnoxious commercial as an example of negative reinforcement), to videos (e.g., of a patient with prosopagnosia), to brief stories (e.g., about how confirmation bias led a man to dismantle a kitchen because he assumed that an electrical stove's whining clock was a trapped kitten), to short summaries of research that illustrate a concept or phenomenon. Beyond their value for enhancing the quality and interest level of classroom lectures, the examples in this book can help teachers find ideas for engaging multiple-choice exam and quiz items. They can also serve as stimuli for writing assignments and small group discussions in which students are asked to come up with additional examples of the concept or phenomenon, or link them to other concepts or phenomena.
Chapter 1: Research Methods and Statistics -- Chapter 2: Biological Aspects of Psychology: Functions and Dysfunctions -- Chapter 3: Sensation and Perception -- Chapter 4: Learning -- Chapter 5: Memory -- Chapter 6: Thinking and Cognitive Abilities -- Chapter 7: Consciousness -- Chapter 8: Motivation and Emotion -- Chapter 9: Development -- Chapter 10: Health, Stress and Coping -- Chapter 11: Personality -- Chapter 12: Psychological Disorders -- Chapter 13: Treatment of Psychological Disorders -- Chapter 14: Social Psychology -- Chapter 15: Industrial/Organizational Psychology.
Keywords: Educational psychology; Teachers-Training of; Education; Psychology-Methodology.; Educational Psychology; Teaching and Teacher Education; Education; Psychological Methods